Hubungan Motivasi dan Kepuasan Kerja terhadap Kinerja Penyuluh Kehutanan - Selfi, Selfi; Golar, Golar; Muis, Hasriani (Universitas Tadulako, 2022)
This research aims to describe and analyze the profile, level of motivation, job satisfaction and performance of forestry instructors at the Lore Lindu National Park Office (LLNPO). The research results show that the profile of forestry instructors is